Foundation for integrating employee health activities for active duty personnel in the Department of Defense - Cecchine, Gary.; Sloss, Elizabeth M.; Nelson, Christopher D.; Fisher, Gail.; Sama, Preethi R.; Pathak, Asha.; Adamson, David M.; National Defense Research Institute (U.S.). Forces and Resources Policy Center; RAND Health; Rand Corporation; United States. Department of Defense. Office of the Secretary of Defense (Santa Monica, CA : RAND, 2009)
If the Department of Defense (DoD) moves toward a more integrated employee health system, a foundation of information about the current system and requisite elements for such integration will be needed. The authors reviewed the research literature and DoD policy documents and interviewed DoD personnel to make several observations about the current state of safety and occupational health (SOH) arrangements in DoD. Currently, SOH policy cuts across several organizations at high levels in the Office of the Secretary of Defense, and SOH programs are implemented by each of the military services. Recently, leadership attention has focused on safety, mostly apart from occupational health, as a separate priority. DoD and the services have made efforts to increase coordination, including both high-level formal councils and through informal relationships among SOH practitioners. Health promotion and wellness have received considerable attention within DoD through periodic health assessments and educational programs, yet these areas have not benefited from the same increased coordination. As DoD contemplates a more integrated approach, the authors considered what DoD might learn from civilian experience with integrating employee health activities. To address this, the authors reviewed civilian models of integration to identify promising approaches and practices that might inform DoD efforts. The review of activities related to employee health in DoD -- including industrial hygiene, safety, health promotion and wellness, occupational health, and its relatively mature health information technology infrastructure -- indicates that there might be little need for DoD to introduce new programs but more need to make use of the information generated by the existing programs in a more coordinated, integrated manner.
Introduction -- Project Goal, Methods, and Definitions -- Safety and Occupational Health in the Department of Defense -- DoD Information Technology Systems Related to Safety and Occupational Health -- Civilian Approaches to Integration -- Observations and Conclusions -- Appendix A: Time Line of Safety and Occupational Health Policies and Programs, 1970-2007 -- Appendix B: Semistructured Interviews with DoD Officials.
"A joint endeavor of RAND Health and the RAND National Defense Research Institute."
"RAND Center for Military Health Policy Research."
"This research was conducted in the RAND National Defense Research Institute"--Preface.
Includes bibliographical references (p. 73-82).
Also available on the internet via WWW in PDF format.
Keywords: Managed care plans (Medical care) -- United States; Medical policy -- United States -- Planning; Medicine, Military -- United States; Occupational health services -- United States; Soldiers -- Medical care -- United States; Military Medicine -- organization & administration -- United States; Occupational Health Services -- organization & administration; Health Promotion -- methods; United States -- Armed Forces -- Medical care -- Management; United States -- Officials and employees -- Health and hygiene